Hustle Culture in Generation Z Study of Thematic Hadith - Permatasari, Murnia Andini; Al Ayubi, Sholahuddin; Makhzumi; Alfariz, Ardan; Waesul Kurni (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
Analyzing the phenomena known as